Sociodemographic disparities in health literacy among American adults: A national survey study - Yiqing “Skylar” Yu; Ana Altares; Alyssa Leib; Laura L. Bellows; Christopher Berry; Dan J. Graham; Megan P. Mueller (Preventive Medicine Reports)
Objectives: Health literacy is associated with various health behaviors and outcomes. The recent distribution of health literacy across different sociodemographic groups in the U.S. is unknown. This study aims to investigate sociodemographic differences in health literacy among U.S. adults using the Newest Vital Sign (NVS) assessment. Methods: We conducted an online survey in 2022 using CloudResearch, involving 2829 participants. This survey included the NVS to measure health literacy and information on sociodemographic factors. Results: Over 60 % of participants demonstrated inadequate (low to moderate) health literacy. Significant associations between health literacy and gender (p < .01), age (p < .01), ethnicity (p = .02), race (p < .01), education level (p < .01), residential region (p < .01), and household income (p = .04) were found. Males, Black or African American, Asian, Hispanic or Latino individuals, those with lower income, and those residing in the Northeast, South, and West regions exhibited lower health literacy compared to their counterparts. Additionally, a positive correlation between age and health literacy was observed, with the highest health literacy level among adults aged 65 and older. Education level showed a non-linear relationship with health literacy, peaking among those with job-specific training post-high school. Conclusion: The study highlights sociodemographic disparities in health literacy. Targeted interventions and policies are needed to address these gaps, improve health outcomes, and reduce economic burdens associated with low health literacy. Future research should consider additional factors, such as digital literacy and language barriers, to provide a more comprehensive understanding of health literacy.